On the Asymmetry of Global Spillovers : Emerging Markets versus Advanced Economies - Arezki, Rabah; Liu, Yang (World Bank, Washington, DC, 2018)
This paper examines growth spillovers between emerging markets and advanced economies. The empirical results, based on a two-bloc setup and cover 1991 to 2015, are twofold. First, the paper shows that the size of the spillovers running from emerging markets to advanced economies is about a fifth of those running from advanced economies to emerging markets. Second, the results point to spillovers from emerging markets to advanced economies having increased over the second half of the sample period. The paper presents suggestive evidence that the (evolving) structure of interdependencies plays an important role in explaining the existence of "asymmetrical spillovers" between these similar size blocs.